2005
DOI: 10.1203/01.pdr.0000182187.88505.49
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Changes in Intraepithelial T Lymphocytes and NK Cells in the Small Intestine of Neonatal Rats

Abstract: The main objective of this study was to characterize developmental changes in small intestinal intraepithelial lymphocyte (IEL) subpopulations during the suckling period, thus contributing to the understanding of the development of diffuse gut-associated lymphoid tissue (GALT) and to the identification of early mechanisms that protect the neonate from the first contact with diet and gut microbial antigens. The study was performed by double labeling and flow cytometry in IEL isolated from the proximal and dista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 39 publications
1
38
0
Order By: Relevance
“…In this sense, in previous studies, we have shown age-related changes in lymphocyte composition and functionality in neonatal rat spleen and mucosal lymphocytes (11,12,22).…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…In this sense, in previous studies, we have shown age-related changes in lymphocyte composition and functionality in neonatal rat spleen and mucosal lymphocytes (11,12,22).…”
Section: Discussionmentioning
confidence: 62%
“…In previous studies, we demonstrated that in early rat life, the intestinal compartment includes a high proportion of NK cells (12,21), which should have an important role in the defense during this stage of development. Current studies also suggest the predominance of IE-NKT during suckling (unpublished observations).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In this sense, cytokine production by human NK cells is different at distinct stages of differentiation; for example, TNFa and GM-CSF are produced throughout differentiation, while type 2 cytokines (IL-13 and IL-5) define NK cells at intermediate stages of the process (Loza et al, 2002;Moretta et al, 2008). The enhancement of NK cell maturation by probiotics present in breast milk could be very important during early life, when the proportion of this subset in intestinal sites is higher than in adults (Pé rez-Cano et al, 2005a, 2005b, and because NK cells play a particularly important role in counteracting infections before acquired immunity is fully developed. Such an effect of breast milk probiotics would complement that of other constituents of breast milk, such as lactoferrin (Pé rez-Cano et al, 2007.…”
Section: Discussionmentioning
confidence: 99%
“…The production of IgA in the suckling mice at 10 days of age may be about 10 times lower than that in adult mice. 18) In a study on rats, the development of IgA bearing lamina propria lymphocytes was delayed until 14 days of age, 19) and the plasma IgA concentration of MR pups at 14 days of age was 2.5 mg/ml, 20) this being approximately 15% of that at 4 wk of age in Sprague-Dawley rats. 21) It is very interesting that the relative thymus weight of the AR-2 pups was respectively significantly larger and smaller than that of the AR-0 and MR pups 10 days after birth (Fig.…”
Section: Discussionmentioning
confidence: 99%